Konflik Norma dalam Pengaturan Pemilahan Sampah - Lawalata, Magreth Syelen; Sedubun, Victor Juzuf; Holle, Erick Stenly (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Government Regulation No. 81 of 2012 article 17 paragraphs (2), (4) and (5), stipulates that The District/City Government provides a means of sorting District/City-scale waste against 5 types of waste. Then, Local Regulation No. 11 of 2015 Article 27 letter f, only requires Local Government of Ambon City to provides waste sorting facilities for 3 types of waste.Purposes of the Research: The purpose of this research is to find out and analyze the conflict of norms in the regulation of Local Regulation No. 11 of 2015 Article 27 letter f with Government Regulation No. 81 of 2012 article 17 paragraphs (2), (4) and (5). The conflict of norms that occurs between the two regulations, interaction is a unilateral conflict of norms and in substantially is a partial conflict of norms.Methods of the Research: This research used normative research method.Results of the Research: Based on the principle of hierarchy, Local Regulation. In fact Local Regulation No. 11 of 2015 Article 27 letter f regulates the type of waste that is not in accordance with Government Regulation No. 81 of 2012 article 17 paragraphs (2), (4) and (5).